1998
DOI: 10.1177/0146167298242002
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Reactivity to Everyday Problems, Affective Inertia, and Neuroticism

Abstract: A naturalistic diary recording study was conducted to assess affective responses to everyday stress. Community-residing male participants made diary recordings regarding problem occurrence and mood several times a day for 8 days. In addition to reporting more frequent daily problems, persons scoring high in neuroticism were more reactive to stressors and were more distressed by recurrent problems than were persons scoring low in neuroticism. New problems affected everyone comparably. There was also evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
373
3
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(398 citation statements)
references
References 47 publications
20
373
3
2
Order By: Relevance
“…Research has demonstrated a central role of N in the reactivity to a variety of threatening cues such as emotional (especially aversive) stimuli (Gross, Sutton, & Ketelaar, 1998;Norris, Larsen, & Cacioppo, 2007), negative feedback (Larsen & Ketelaar, 1989) and the occurrence of daily problems (Suls, Green, & Hillis, 1998). This evidence is consistent with a conceptualization of N as tapping into people's predisposition to react vigilantly to threatening cues.…”
Section: The Ecological Salience Of Social Inclusionsupporting
confidence: 62%
“…Research has demonstrated a central role of N in the reactivity to a variety of threatening cues such as emotional (especially aversive) stimuli (Gross, Sutton, & Ketelaar, 1998;Norris, Larsen, & Cacioppo, 2007), negative feedback (Larsen & Ketelaar, 1989) and the occurrence of daily problems (Suls, Green, & Hillis, 1998). This evidence is consistent with a conceptualization of N as tapping into people's predisposition to react vigilantly to threatening cues.…”
Section: The Ecological Salience Of Social Inclusionsupporting
confidence: 62%
“…For example, individuals high in Neuroticism experience more stressful events, whereas those high in Extraversion experience both more stressful and more pleasurable events (Bolger and Schilling, 1991;Fergusson and Horwood, 1987;Magnus et al, 1993;Suls et al, 1998). Moreover, Neuroticism predisposes people to experience negative emotions and distress, regardless of level of stress (Bolger and Schilling, 1991;Watson and Clark, 1984.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who are emotionally unstable describe themselves as emotional, impatient with others, and intolerant toward ambiguous situations (De Caroli & Sagone, 2009). They are also more likely to experience negative emotions such as anxiety, fear, depression, or irritability (Suls, Green, & Hillis, 1998). Several studies found a positive association between emotional instability and creativity (e.g.…”
mentioning
confidence: 99%